Spiritual care and kidney disease in NZ: A qualitative study with New Zealand renal specialists. Issue 11 (November 2014) - Egan, Richard; MacLeod, Rod; Tiatia, Ramona; Wood, Sarah; Mountier, Jane; Walker, Rob
Abstract Aim People with chronic kidney disease have a shortened life expectancy and carry a high symptom burden. Research suggests that attending to renal patients' spiritual needs may contribute to an improvement in their quality of life. The aim of this qualitative study was to investigate the provision of spiritual care in New Zealand renal units from the perspective of specialists. Methods The study followed a generic qualitative approach and included semi‐structured interviews with specialists recruited from New Zealand's ten renal centres. Results Five specialist doctors and nine specialist nurses were recruited for interviews. Understandings of spirituality were broad, with most participants having an inclusive understanding. Patients' spiritual needs were generally acknowledged and respected though formal spiritual assessments were not done. Consideration of death was discussed as an often‐unexamined need. The dominant position was that the specialists did not provide explicit spiritual care of patients but there was some ad hoc provision offered through pre‐dialysis educators, family meetings, Māori liaison staff members and the efforts of individuals. Chaplains were well used in some services. Participants had received no pre and little in‐service training or education in spiritual care. Suggestions for improvements included in‐service training, better utilization of chaplaincy services and training in advance care planning. Conclusion Most participants indicated they would attempt to provide some form of spiritual care, either directly or by referring the patient to appropriate services. However, participants generally demonstrated a lack of confidence in addressing a patient's spiritual needs.